Aplikasi E-Patient Pada Klinik X - Hilarius Andriano Sengyang; Yulia Yulia; Silvia Rostianingsih (Jurnal Infra, 2020)
Currently X Clinic has many patients, it causes ineffective service to patients, where there are a lot of queues without any clarity of the estimated queue waiting time. Besides, most of the activities in the clinic such as medical records, laboratory requests, and prescriptions are still done manually so that is increases the risk of being scattered.Looking the background of the problem, an application designed to handle patient queues equipped with the sms gateway feature to give information about queue registration. The application is created with Node.js and React.js.The results obtained from this application include handling patient queues, with estimated queue waiting time via SMS gateway, recording master data including medical records, laboratories, and prescriptions.